Teacher’s Perceptions of Islamic Science Learning Using a Scientific Approach Assisted by “Selawat Science” - Yuniar Fahmi Lathif; Sarwi Sarwi; Putut Marwoto; Endang Susilaningsih (Universitas Negeri Semarang, 2021)
This study aims to describe the teacher's perception of learning science with a scientific approach assisted by